Determination of Autophagic Activity Of J774a.1 Murine Macrophages Infected With Recombinant Mycobacterium Smegmatis - Nur Ayuni, Kadir; Maria, E Sarmiento; Armando, Acosta; Norazmi, Mohd-Nor (2019)
Tuberculosis (TB) remains a major worldwide health problem which causes more than 1.3 million deaths annually. The development of a new vaccine as a replacement of Bacille Calmette Guerin (BCG) or to improve its efficacy is one of the goals mooted by the World Health Organization (WHO) to control TB. Mycobacterium smegmatis (M. smegmatis) is nonpathogenic and commensal in humans, which shares many characteristics with Mycobacterium tuberculosis (M. tuberculosis). Mycobacterial vectors including M. smegmatis have been successfully used in the development of experimental vaccines against TB. In the current study, recombinant M. smegmatis expressing selected Ag85B epitopes (P1, P2 and P3) was constructed (rMs064). Autophagy play important role in delivery of the intracellular bacteria to simulate the adaptive immune response. Targeting the autophagy mechanism is a viable approach to enhance the specific immune response leading to the prevention of new infection or reactivation of latent TB. Therefore, autophagy modulation of J774A.1 murine macrophages was determined after infection with rMs064 by monitoring the LC3B-II level by flow cytometry and western blot. This experiment allows the determination of autophagy modulation as well as the autophagic flux induced by rMs064 on J774A.1 macrophages. The results of both assays showed the LC3B-II level were not significantly increased compared to uninfected macrophages. In conclusion, macrophage activation and cytokine stimulation may be required for optimal autophagy monitoring assays that can be modulated by rMs064.